Socio-Economic Determinants of Household Food Expenditure in a Low Income Township in South Africa - Sekhampu, Tshediso Joseph (Mediterranean Journal of Social Sciences, 2012)
The study, on which this article is based analysed the impact of selected socio-economic characteristics on food expenditurepatterns of a low-income township in South Africa. The results are based on a household survey using questionnaires. A multipleregression model was used to explain responses in monthly household food expenditures to socioeconomic factors. Household income,household size, age, employment status, and the educational attainment of the household head were found to exert a strong positiveimpact on food expenditures. The marital status of the household head was associated with a negative impact on household foodexpenditure, and the coefficient for the variable was significant. Household size, employment and marital status of the household headare the most significant predictors of food expenditure. The gender of the household head had no significant impact on household foodexpenditure. This study contributes to the understanding of low income townships in South Africa by modelling the factors influencinghousehold food expenditure.